Functional analysis of the mammalian RNA ligase for IRE1 in the unfolded protein response - Poothong, Juthakorn (Biosci Rep, 2017)
The unfolded protein response (UPR) is a conserved signalling pathway activated on the accumulation of unfolded proteins within the endoplasmic reticulum (ER), termed ER stress. Upon ER stress, HAC1/XBP1 undergoes exon/intron-specific excision by inositol requiring enzyme 1 (IRE1) to remove an intron and liberate the 5′ and 3′ exons. In yeast, the 5′ and 3′ HAC1 exons are subsequently ligated by tRNA ligase (Rlg1p), whereas XBP1 ligation in mammalian cells is catalysed by a recently identified ligase, RtcB. In the present study, RNA ligase activity of the human RtcB (hRtcB) involved in the unconventional splicing of XBP1/HAC1 mRNA was explored in an rlg1-100 mutant yeast strain. Distinct from Escherichia coli RtcB and Rlg1p, expression of hRtcB alone inefficiently complemented HAC1/XBP1 splicing and the hRtcB cofactor (archease) was required to promote enzymatic activity of hRtcB to catalyse RNA ligation.